Working from home: Findings and prospects for further research. (August 2022) - Kaiser, Stephan; Suess, Stefan; Cohen, Rachel; Mikkelsen, Elisabeth Naima; Pedersen, Anne Reff
Working from home has not only attracted attention during the Covid-19 pandemic but has been researched for a long time in connection with topics such as the flexibilization of work, digitalisation and changing values. Central issues around the organisational and societal phenomenon of working from home are linked to the resources and strains of employees. This has direct consequences for the leadership and management of human resources. In this article, we review the results of research contributions available in this issue and at the same time show that working from home raises even broader questions, for example about the emergence of new hybrid forms of organisation and employment or social justice or new infrastructures for living and working.